Perforación espontánea del colédoco en el niño - do Campo, Magela; Guiguens, Marcos (Cirugía del Uruguay, 1994)
The author presents a clinical case of spontaneous choledocus perforation in a 9 month old infant whose symptoms consisted of vomiting, neuropsychical depression, fever, and abdominal distension.